Safeguarding the Caribbean's future: making the case to research the direct and indirect impacts of climate change on youth mental health and wellbeing - Holdsworth, Jaclyn; Hunte, Shelly-Ann; Barker, Kershelle; Sherin, Jonathan; Rao, Mala; Maharaj, Sandeep B. (Frontiers in Public Health, 2023)
This article makes a call for attention to paid on the development of a research agenda for studying the impact of climatic events on youth mental health in the Caribbean. It details the climate injustices that the region faces and the potential mental health problem which can arise from climatic events. It makes a call for interdisciplinary research and a multi stakeholder approach to dealing with this potential issue.